DESA TANGGUNG BENCANA DAN PERUBAHAN IKLIM - Parebalangla, Wilda; Ardiansyah; Jumarni; Annisa; Fadilah, Nur; S, Suci Purnama.; Saputra, M. Nur Firda; Munir, Ahmad Syahidul Haq; Israini; Muhammad, Fuad; Ramadani, Syahri; Raslim; Purniawan, Didin (Jurnal Pengabdian Indonesia (JPI), 2026)
The Community Service Program (Kuliah Kerja Nyata/KKN) Post 21 of the Disaster-Resilient Village was implemented in Buntu Kunyi Village, Suli District, Luwu Regency as an effort to enhance community capacity in facing disaster risks and the impacts of climate change. Buntu Kunyi Village has a relatively high level of vulnerability to disasters such as landslides and floods, thus requiring a systematic and sustainable empowerment approach. This KKN program applied the Asset-Based Community Development (ABCD) method, which emphasizes the utilization of local potential and community participation. The stages implemented included discovery, design, define, and reflection, resulting in village asset mapping, needs-based program planning, and a comprehensive evaluation of program implementation. Three main programs were carried out: the preparation of evacuation maps, the development of disaster education modules, and the documentation of environmental action activities. The results of the program showed a significant increase in disaster literacy, community preparedness, and citizen participation in environmental conservation as a form of adaptation to climate change. Overall, this KKN program contributed to strengthening the resilience of Buntu Kunyi Village through collaboration between students and the community in building independent and sustainable disaster risk mitigation.